Penerapan Model REACT terhadap Pemahaman Konsep Siswa Kelas XI SMA - Lilis Ayu Lestari; Rachmat Sahputra; Ira Lestari (Orbital: Jurnal Pendidikan Kimia, 2021)
This study aims to determine differences in conceptual understanding of students who are taught using the Relating, Experiencing, Applying, Cooperating, Transfering (REACT) model with students who are taught using conventional models and to describe the improvement in conceptual understanding of students in class XI SMA Kemala Bhayangkari on Acid Basa material. The form of research used was a quasi experimental design with a nonequivalent control group design research design. The population in this study were all students of class XI MIA SMA Kemala Bhayangkari Kubu Raya for the academic year 2019/2020, totaling 62 students. The sample selection technique was carried out by simple random sampling. The data collection technique used was a test of students' conceptual understanding. Data analysis used Shapiro-Wilk test, Levene statistic, U-Mann Whitney and N-Gain calculation. The results of data analysis using the U-Mann Whitney test obtained an asymp.sig (2-tailed) value of 0.208, which means that there are differences in conceptual understanding between students taught using the REACT model and students taught using conventional models.. Based on the N-Gain calculation, it is known that the REACT model can improve students' conceptual understanding by 0.42 in the moderate category.